Effects of Electrical Stimulation and Simulated Conventional- and Extended Chilling Method on Cooked Chicken Breast Meat Texture and Yield - Young, L.L.; Cason, J.A.; Smith, D.P.; Lyon, C.E.; Dickens, J.A.; Walker, J.M. (International Journal of Poultry Science, 2005)
This study was conducted to determine effects of carcass electrical stimulation and alternative carcass chilling methods on texture and yield of early-harvested boneless broiler-breast fillets. New York dressed broiler carcasses were electrically stimulated for 90 s immediately after defeathering. Control carcasses were held similarly for 90 s but not stimulated. After evisceration, half the stimulated and half the control carcasses were chilled for 3 h in ice-water (extended immersion chilled). Remaining carcasses were chilled in ice-water for 1 h and then stored for an additional 2 h (conventionally chilled). Breast fillets (Pectoralis major muscles) were manually harvested immediately after chilling (3.5 h post-mortem). After weighing and overnight storage, all muscles were cooked and evaluated for shear values and cooked yields. Fillets from stimulated carcasses required significantly less force to shear and exhibited greater cooked yields than those from non-stimulated carcasses. Fillets from conventionally chilled carcasses exhibited greater yield than those from extended chilled carcasses, but chilling method did not affect shear values.